Fabrication and Study the Structure, Optical and Dispersion Parameters of PMMA with InCl3 Additive - Nadir Fadhil Habubi (Journal of Global Pharma Technology, 2016)
Polymethyl methacrylate films are prepared by casting method with various content of InCl3 (2, 4%). X-ray diffraction (XRD) and optical microscope are used to determine the structural properties. Transmittance that determined using UV-Visible spectrophotometer and optical parameters also calculated. Urbach energy values increase with the increasing of InCl3 and energy gap decreased from 3.849 eV of pure PMMA films to 3.230 eV of PMMA-4% InCl3. Dispersion parameters are determined using Wemple-DiDomenico model. Refractive index data at infinite wavelength was found to obey single oscillator model.Keywords: PMMA, Dispersion parameters, Composite, Optical properties.